2003
DOI: 10.1124/jpet.102.045740
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Treatment with Vitamin E on Endothelial Dysfunction in a Type I in Vivo Diabetes Mellitus Model and in Vitro

Abstract: Diabetes mellitus often leads to generalized vasculopathy. Because of the pathophysiological role of free radicals we investigated the effects of vitamin E. Twenty-eight rats were rendered diabetic by streptozotocin injection and were fed either with a diet with low (10 mg/kg of chow), medium (75 mg/kg of chow) or high amounts of vitamin E (1300 mg/kg of chow). Nine age-matched nondiabetic rats receiving 75 mg of vitamin E/kg chow served as controls. After 7 months, mesenteric microcirculation was investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…The animals did not receive an antidiabetic treatment. Diabetic rats had stable, moderate hyperglycemia throughout the 2 months (mean blood glucose concentrations, Ͼ400 mg/dl) (Dhein et al, 2003). After 2 months, the experiment was terminated.…”
Section: Methodsmentioning
confidence: 99%
“…The animals did not receive an antidiabetic treatment. Diabetic rats had stable, moderate hyperglycemia throughout the 2 months (mean blood glucose concentrations, Ͼ400 mg/dl) (Dhein et al, 2003). After 2 months, the experiment was terminated.…”
Section: Methodsmentioning
confidence: 99%
“…The animals did not receive an antidiabetic treatment. Diabetic rats had stable moderate hyperglycemia throughout the 2 months (mean blood glucose concentrations Ͼ400 mg/dl) (19). After 2 months the experiment was terminated.…”
Section: Methodsmentioning
confidence: 99%
“…In isolated mesenteric beds of Wistar rats with diabetes for 6 months, a reduction in endothelium-dependent relaxation was found (22). In addition, cultures of porcine aortic endothelial cells (PAECs) submitted to high-glucose concentrations showed an endothelial dysfunction mediated by hyperglycemia, which was revealed by reduced endothelial NO production or release (22)(23), as well as severe changes in endothelial cell structure (24). More recently, several studies suggested plasma glucose fluctuations and glucose peaks, such as those occurring in the postabsorptive state, to provide a strong contribution to the development of endothelial dysfunction (25)(26)(27).…”
Section: Cardiovascular Datamentioning
confidence: 99%